Biblia w wileńskim "Słowniku języka polskiego" / Małgorzata B. Majewska. - Majewska, Małgorzata Brygida
Keywords: The Bible, the Vilnius "Dictionary of Polish language", dictionary content digitalization, dictionary database digitalization.